2016
DOI: 10.1097/sla.0000000000001216
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Surgical Decision-making Processes for Contralateral Prophylactic Mastectomy in Women With Breast Cancer

Abstract: Structured Abstract Objective We prospectively examined the psychosocial predictors and the decision-making process regarding contralateral prophylactic mastectomy (CPM) among women with sporadic breast cancer. Summary Background Data Increasing numbers of women with breast cancer are seeking CPM. Data are limited about the surgical decision-making process and the psychosocial factors that influence interest in CPM. Methods Women with early stage unilateral breast cancer (n=117) were recruited before thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 53 publications
(50 reference statements)
3
54
2
Order By: Relevance
“…Multiple investigators have cited anxiety as an important factor in the decision making process for women to choose CPM, 21, 22, 23 but few have directly measured preoperative anxiety levels using validated PRO instruments. 24, 25 A prospective questionnaire based study on the surgical decision-making process for CPM showed that patients with less knowledge about breast cancer and greater worry were more interested in CPM. 25 Greater cancer worry ultimately was a significant predictor for patients who went on to have CPM.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigators have cited anxiety as an important factor in the decision making process for women to choose CPM, 21, 22, 23 but few have directly measured preoperative anxiety levels using validated PRO instruments. 24, 25 A prospective questionnaire based study on the surgical decision-making process for CPM showed that patients with less knowledge about breast cancer and greater worry were more interested in CPM. 25 Greater cancer worry ultimately was a significant predictor for patients who went on to have CPM.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, more than 50 % of women with sporadic breast cancer were initially interested in CPM, but only 10 % underwent CPM 39. Although patients claim CPM discussion rates of 45–80 % with their doctor, only half of patients relay that their doctors outlined reasons not to have CPM 38,39. Given that approximately one-third of patients in one study experienced worse than expected results, this discussion may serve as an educational opportunity for providers to optimize informed consent 20.…”
Section: Shared Decision Making For Cpmmentioning
confidence: 99%
“…Surgeons should encourage patients to actively participate in the decision-making process and try to elicit patient’s treatment preferences. Since many patients consider CPM somewhere in their decision-making process, surgeons should make a recommendation based on their expert opinion after weighing the evidence and reviewing the risks and benefits of CPM with the patient 39. The surgeon is responsible for informing the patient about CPM’s impact on outcomes, both physical and psychological, engaging the patient in the decision-making process, and ensuring that patients are making treatment decisions that are concordant with their personal values and goals.…”
Section: Counseling Patients On Contralateral Prophylactic Mastectomymentioning
confidence: 99%
“…Indeed, in almost all studies on the topic, fear of and desire to avoid recurrence and ''peace of mind'' are oft-cited reasons by women who choose to undergo CPM. 9,10 These emotional factors may conflate not only the perceived risk of second malignancy but whatever survival benefit CPM provides. These factors may contribute to the internal dissonance in women who may objectively understand the data around CPM but subjectively feel compelled nonetheless to pursue a CPM.…”
Section: 2mentioning
confidence: 99%